Relationship between the Biological Clock and Inflammatory Bowel Disease - Jonathan Giebfried; Axel Lorentz (Clocks & Sleep, 2023)
The biological clock is a molecular oscillator that generates a 24-hour rhythm in accordance with the earth’s rotation. Physiological functions and pathophysiological processes such as inflammatory bowel diseases (IBD) are closely linked to the molecular clock. This review summarizes 14 studies in humans and mice on the interactions between the biological clock and IBD. It provides evidence that IBD negatively affect core clock gene expression, metabolism and immune functions. On the other hand, disruption of the clock promotes inflammation. Overexpression of clock genes can lead to inhibition of inflammatory processes, while silencing of clock genes can lead to irreversible disease activity. In both human and mouse studies, IBD and circadian rhythms have been shown to influence each other. Further research is needed to understand the exact mechanisms and to develop potential rhythm-related therapies to improve IBD.